Práticas de leitura para alunos da 2ª etapa da educação de jovens e adultos da escola Maximiano Antônio Rodrigues Abaetetuba-PA - GOMES, Luzinete do Socorro Rodrigues (2023)
The main objective of this work is to read the book "The adventures of the boy Boto: the hero of the Amazon" with students of the 2nd stage of the education of young people and adults of the school Maximiano Antônio Rodrigues, municipality of Abaetetuba, applying several reading practices and reflecting on student reading strategies and analogies. In order to carry out this reflection, he sought as principal source Antonio Candido an author who refers to the importance of literature for the formation of man, and traces a great discussion about literature as a citizen's right. There is still in this work a brief approach on the history of youth and adult education this modality of education regulated by article 37 of Law 9394 of December 20, 1996. It also brings the activities applied to said students, as well as reflections on the practices and analogies used by the students to carry out the reading of the work in question.